As perspectivas da representação substantiva sobre a ação parlamentar feminina no Brasil - Silva, Ana Paula Cavalcante Limão da (2019)
This thesis proposes to present a mapping of the parliamentary profile of the deputies who assumed mandates in the 2003-2007, 2007-2011 and 2011-2015 legislatures, through the analysis of the legislative production of these women, highlighting the proposition of draft laws, in order to verify the extent to which female parliamentary action results in substantive representation in the Brazilian Federal Legislative Chamber. This research is based on a theoretical debate on the main conceptions of political representation, with emphasis on substantive representation and its consequences in the political space. Thus, the substantive representation is considered from the representative's activity, that is, from the content of the political action of that leader and what is its correspondence with the interests of the electorate. The data of this work were collected in the Chamber of Deputies Portal, identifying the naturalness and party bond of the deputies, number of bills proposed by each parliamentarian, type of authorship of the proposition, status of the matter in the legislative process and in the case of propositions archived, the reason for this archiving was collected. It was also verified the content of each proposed project and based on the committees that debated the matter, a classification of 27 themes addressed by the deputies in their projects was defined. This thesis shows that parliamentarians propose a number of projects commensurate with their male counterparts, more than 50% of the propositions are the sole author and, as far as the proposition themes are concerned, the areas related to “care” and to the same extent “hard” such as labor, economics, finance and taxation, administration and public service. Regarding the themes on feminist and women's agendas, they add up to a percentage of only 12% of propositions presented, and it appears that these matters address issues related to work, women's health and violence against women. In short, female underrepresentation in politics is a barrier to be broken, about women elected identify important advances in their parliamentary performance, they are debating issues considered masculine and present an autonomous performance in Parliament, so this research points to importance of the presence of minority groups in elected positions. In the case of deputies, the increased female presence in this political space strengthens women's substantive representation, and can contribute to gender issues on the agendas of parliamentarians of both sexes.